Relationship between sleep quality and quantity and lower-body neuromuscular performance characteristics in semi-professional male basketball players - Damjana V. Cabarkapa; Dimitrije Cabarkapa; Andrew C. Fry (Frontiers Media S.A., 2024)
Sleep has been recognized as one of the most essential recovery methods necessary for achieving optimal performance. However, there is still a lack of scientific literature focused on examining its impact on one of the most prevalent skills in the game of basketball, the countermovement vertical jump (CVJ). Therefore, the purpose of the present study was to examine the relationship between sleep quality and quantity, and lower-body neuromuscular performance characteristics within a cohort of semi-professional male basketball players. Twenty-eight athletes competing in a first-tier regional league in Serbia volunteered to participate in this investigation. Upon arrival at the gym, all athletes completed the Pittsburgh Sleep Quality Index (PSQI) self-rated questionnaire. Immediately after completion of the PSQI, each athlete stepped on a force plate system and performed three maximum-effort CVJs with no arm swing. The following force-time metrics were obtained for the analysis: eccentric and concentric absolute and relative mean and peak force and power, vertical jump height, and reactive strength index-modified. Pearson product-moment correlation coefficients were used to examine the strength of the linear relationships between sleep quality and quantity and lower-body neuromuscular performance characteristics (p < 0.05). The results indicated that sleep quality appears to have a greater impact on the concentric than the eccentric phase of the CVJ (e.g., concentric mean force [r = −0.830; p < 0.001], relative concentric peak force [r = −0.466; p = 0.013, eccentric mean power (r = −0.162; p = 0.409)], while no significant relationship was found between sleep quantity and lower-body neuromuscular performance (e.g., concentric peak force [r = −0.055; p = 0.782], relative eccentric mean power [r = −0.301; p = 0.107]). Overall, these findings offer valuable insights into the importance of good sleep hygiene (e.g., efficiency, duration) in an athletic population, and can help practitioners develop more effective training and recovery programs.